The Concept of Truth in the Law - Lastauskienė, Giedrė (Teisė, 2023)
The article analyses the role of facts in the Law and examines the standards of proof of facts. It examines the prevalence of the use of the concepts of objective, formal and material truth as the purpose of proof in the Lithuanian legal regulation, legal literature and jurisprudence and assesses the correctness of the use of these concepts. The peculiarities of the standard of proof of facts in cases of constitutional justice are discussed.
Keywords: law; facts; truth; objective truth; formal truth; material truth; proof